2008
DOI: 10.1136/jme.2007.023119
|View full text |Cite
|
Sign up to set email alerts
|

The ethics of paediatric anti-depressant use: erring on the side of caution

Abstract: This paper aims to outline the ethical concerns regarding the use of antidepressant medication in children and adolescents. Recent debates surrounding this issue have focused on the link between selective serotonin reuptake inhibitor use and an increased risk of suicidal thinking/behaviour, and weighed that against the benefit of the alleviation of depressive symptoms. It is argued here that such an approach is simplistic. There are several serious risks surrounding antidepressant use in the young that ought t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…At a time when ethicists have argued that antidepressant prescription to pediatric patients should be “severely restricted” (Shearer and Bermingham, 2008), interventions with potential to reduce depressive symptoms and suicidality in adolescent MDD are urgently required. Long studied as an ergogenic supplement for athletic skeletal muscle performance, it is now clear that creatine plays a vital role in brain function (Brosnan and Brosnan, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…At a time when ethicists have argued that antidepressant prescription to pediatric patients should be “severely restricted” (Shearer and Bermingham, 2008), interventions with potential to reduce depressive symptoms and suicidality in adolescent MDD are urgently required. Long studied as an ergogenic supplement for athletic skeletal muscle performance, it is now clear that creatine plays a vital role in brain function (Brosnan and Brosnan, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Bianchi et al [18] reported that fluoxetine treatment in Ts65Dn mice improves cognitive ability. Although these medications are commonly prescribed, studies have shown that fluoxetine can increase the risk of suicidal thinking/behavior [19] and that lithium can be toxic to the renal system [20]. Therefore, the potential risk of these treatments on patients with DS may outweigh the clinical benefit.…”
Section: Introductionmentioning
confidence: 99%